Erosive acute colitis associated with intestinal spirochetosis - Fabio Dantas de Paula; Glicia Estevam de Abreu; Maiara Ferreira de Souza; Luiz Antonio Rodrigues de Freitas; Daniel Abensur Athanazio (BMC, 2021)
Abstract Background Although usually believed to be harmless, intestinal spirochetosis may active erosive colitis associated with intestinal spirochetosis that may mimic idiopathic chronic inflammatory bowel disease. Case presentation. A 49-year-old homosexual male patient sought medical assistance due to asthenia, rectal bleeding, tenesmus, and diarrhea for one month. He had been using corticosteroids for nine months to treat sciatic nerve pain. Colonoscopy showed rectum and distal sigmoid with diffuse erythema with many surface erosions. Rectal biopsy showed inflammatory changes including chronic changes such as architectural distortion and basal plasmacytosis, and active inflammation including crypt microabscesses. In all large bowel sample, dense colonization of intestinal spirochetosis was observed. Patient also had a positive PCR testing for Chlamydia trachomatis. The patient was treated with metronidazole for 14 days, ciprofloxacin for 14 days and azithromycin (single dose). Symptoms improved and the patient is asymptomatic after two months of follow-up. Conclusion In some high-risk groups, intestinal spirochetosis may cause colonic manifestations with overlapping features with intestinal bowel diseases. Awareness of this association is importance since proper antibiotic therapy against Brachyspira (metronidazole) is highly effective. Coinfection with other sexually transmitted infections is common and proper treatment is required.